Revolutionizing Education 4.0: Evaluating the Role of Robots in Learning Effectiveness - Umbara Destie Monikha Austriya (E3S Web of Conferences, 2024)
To address the challenges for society in using a wide range of knowledge and skills to find creative solutions using new, constantly evolving technologies, Education 4.0 proposes a transformative approach that integrates Industry 4.0 technologies and different teaching methods. This paradigm envisions personalized learning through real-time learner profiling and emphasizes the integration of robots in higher education, offering unprecedented opportunities to enhance learning experiences and skill development. Previous research shows that educational robots are becoming a significant technological tool, drawing interest among students for further exploration.The study aims to explore the historical development, types of robots used, and prominent themes and applications in higher education, providing valuable insights to educators, researchers, and policymakers. The study utilizes VOSviewer to visually present research on teacher leadership styles, analyzing articles from 1990 to 2023 and identifying five clusters of keywords. Keywords like “robotics,” “student,” and “engineering education” were prevalent. Recent discussions included keywords like “high education,” “Virtual reality,” “Intelligent robots,” and “Educational innovations.” Over the past decade, articles on robots in higher education have significantly increased, with Spain and the United States being major contributors to this field. The findings suggest that robots hold great potential in revolutionizing education, providing interactive and engaging experiences beyond traditional methods